Business investment decision (BID) tool for RTB seed enterprises - Rajendran, S.; Reddy, J.; Ogero, K.; Ogwal, M.; Mayanja, S.; Afuape, S. (2025)
This brief introduces the Business Investment Decision (BID) Tool, an automated and gender-responsive digital solution designed to help RTB (Roots, Tubers, and Bananas) seed enterprises develop bankable and scalable business plans. The tool connects operational, financial, and investment decisions for seed producers ranging from public research institutions (NARIs) to private cooperatives and commercial seed companies. It enables enterprise modeling across pre-basic, basic, certified, and QDS stages, transforming operational data into financial statements, profitability metrics (NPV, IRR, ROI), and investment readiness indicators. Initially developed in Excel, the tool was later digitized by MOOD Technologies (Uganda) to create a web-based version (http://bidtool.cipotato.org ). It has been validated in Uganda, Tanzania, Kenya, Nigeria, and India, supporting seed enterprises such as BUSECO, CHAWAVITA, GoSeed, and RTB-EAGEL. The BID tool helps seed producers design inclusive, data-driven, and financially sound business models for sustainable RTB seed systems